Post a New Question


posted by on .

I can only manipulate one side of the equation and the end result should be equal to the other side. please help.

((sinx + cosx)/(1 + tanx))^2 + ((sinx - cosx)/(1 - cotx))^2 = 1

  • Math - ,

    since there's only one side that needs manipulating, I'd pick the left side. :-)

    1+tan = (sin+cos)/cos and
    1-cot = (sin-cos)/sin

    we have

    [(sin+cos)*cos/(sin+cos)]^2 + [(sin-cos)*sin/(sin-cos)]^2

    = sin^2+cos^2
    = 1

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question